Analysis of work cocitation on indexing language in BRAPCI's database - Tolare, Jéssica Beatriz; Fujita, Mariângela Spotti Lopes; Santos Júnior, Edmilson Alves dos (Informação em Pauta, 2020)
In order to verify the scientific development of the indexing language theme, a bibliometric analysis of scientific production was carried out, from 2008 to 2019, in the Database in Information Science (BRAPCI). To carry out this analysis, Bibliometric methods were used, based on the search for research in the database mentioned with the compound term “indexing language”, focusing on the most productive authors and their co-quotation relationships. A sample of 64 articles was constituted with 885 authors, with emphasis on the first 12 authors who had more than 10 citations. The authors with the highest productivity rates have at least 5 citations, while all authors have at least one citation related to another author. Thus, it was possible to trace the most productive authors, the most cited authors and the most relevant journals. With that, the co-authorship network was created, making it possible to visualize the relationships between the authors. Therefore, it is necessary to emphasize the importance of analyzing the production of the area, as it allows the observation, analysis, data collection, identification and interpretation of how it has been developing, specifically.